Self-efficacy and Caring Behavior of Nurses in the Inpatient Room of a Local Government Hospital - Hasnidar; Afrida; Wahyuni, Sri (Bantayang Omni Cendekia, 2024)
Background: Nurses have a great influence in nursing services in hospitals through a caring attitude by providing services that are much better than other health workers by paying attention to humanistic values so as to improve a harmonious relationship between nurses and patients. Self-efficacy acts as one of the factors that influence the caring attitude of nurses. Objective: This study aimed to know the relationship between self-efficacy and caring behavior of nurses in the inpatient room of a local government hospital. Methods: This study used quantitative design with a cross-sectional approach. The sample of this study was 46 respondents obtained by stratified random sampling technique. Data collection was carried out using questionnaires and analyzed using the Chi-square test. Results: Of 46 respondents, the majority had high self-efficacy and caring behavior, which were 36 (78.3%) and 23 (50%) respondents respectively. The Chi-square test showed that the p-value was 0.012 (< 0.05), indicating that there was a relationship between self-efficacy and caring behavior of nurses in the inpatient room of a local government hospital. Conclusion: There is a relationship between self-efficacy and caring behavior of nurses in the inpatient room of a local government hospital.